SURVAI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK KABUPATEN BEREBES - Agus Suroso (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
This research is intended to evaluate the performance of public service from external perspective. Accordingly, the study approach employed is to get feedback from both individuals and business sector as consumers of the public service rendered by the local government. The aims of the study are to get data and information on the degree of the usage of public service, to identify factors influencing public dissatisfaction after consuming service, and to identify the causes of not consuming service. The study employs survey method and the sample size are 505 and 150 for non-business individuals and business sector, respectively. The sample saize of non-business individuals is assumed to be enough compared with that recommended by the Depdagri guidance. The conclusion drawn from the findings is the Local Government of Brebes needs to formulate several steps to improve all public service sectors. Generally, however, the proportion of the respondents’ satisfaction is higher than that of dissatisfied respondent. Many reasons that cause the respondent not using the service indicate the inefficiency of Brebes Government in providing the public services. The Local Government of Brebes also needs to show his commitment and real effort to handle a lot of real issues as stated in the general questions, so that the people’s attitude and trust to the Local Government of Brebes will increase.